Dīwān-i Ishrāq - Dāmād, Mīr (Miras Maktoob, ISBN: 9789004365452., 2019)
In early Islamic philosophy, poetry was regarded as a means to transmit the eternal truths of philosophy to the masses and to move them to virtuous conduct by the use of poetical syllogisms. We find this theory for the first time in the works of Abū Naṣr al-Fārābī (d. 339/950). In another application, poetry was used as a didactic tool in the philosophical curriculum, like Avicenna's (d. 428/1037) Urjūza fi ʼl-manṭiq or, much later, Mullā Hādī Sabzavārī's (d. 1289/1873) Manẓūma on logic and philosophy. Finally, there are the many poems which, while philosophical in spirit, were not written to be learned by heart by others but rather from personal motives. Here we can mention some of the Persian poetry ascribed to Avicenna or the philosophical poetry of Nāṣir Khusraw (d. 481/1088). The poems in this collection by Mīr Dāmād (d. 1040/1631), a prominent member of the Isfahan School in philosophy, belong to this latter category.